SOSIALISASI DAMPAK BAIK MENDONORKAN DARAH SUKARELA KE INSTALASI TRANSFUSI DARAH: SOCIALIZATION OF THE GOOD IMPACT OF VOLUNTARY BLOOD DONATION TO BLOOD TRANSFUSION INSTALLATIONS - Laeli Farkhah (Jurnal Pengabdian Masyarakat Kesosi, 2020)
The importance of the availability of blood to meet the need for blood transfusions that can occur at any time such as for accident victims, patients with major surgery such as heart surgery, cesarean section, and for people with blood diseases such as hemophilia and thalassemia. Therefore, it is very important to know what factors can influence a person to donate blood voluntarily and regularly. This service aims to socialize the factors that influence voluntary donors to donate blood regularly, namely characteristics, sources of information, attitudes, reference groups, intentions and actions of voluntary donors to donate blood at UTD-PMI Kramat Raya Central Jakarta. This service is based on research conducted at UTD-PMI Kramat Raya, Central Jakarta by taking samples from parties who donate blood there.